Modern Criteria for Ensuring Tourism Security as an Element of National Security - Azizova Nazira Tokhtayevna; Farkhodova Shohnoza Umidbek qizi (Scientific Trends, 2025)
The article discusses the features of the organization of the national security system in tourism and the criteria for its effectiveness. Based on the application of the systematic research method, the categorical apparatus and the main directions of the development of the integrated security system of the tourist and recreational industry of the O’zbekistan are analyzed taking into account the current set of external and internal factors, as well as the global transformation of the world market of tourist and recreational services at the present stage. Ways are proposed to increase the effectiveness of the constant safety of internal and external tourists on the basis of state regulation and management, achieve sustainable safe competitive status and comprehensively use the competitive advantages of tourism, and respond adequately to emerging threats.
Keywords: Development trends in tourism, growth prospects, comprehensive security, means of diversifying security measures, comprehensive approach to improvement, international cooperation.